HDP-101, an anti-BCMA antibody-drug conjugate, safely delivers amanitin to induce cell death in proliferating and resting multiple myeloma cells - Figueroa Vazquez, Vianihuini; Ko, Jonathan; Breunig, Christian; Baumann, Anja; Giesen, Nicola; Palfi, Aniko; Müller, Christoph; Lutz, Christian; Hechler, Torsten; Kulke, Michael; Müller-Tidow, Carsten; Krämer, Alwin; et al. (Molecular cancer therapeutics, 2021)
Despite major treatment advances in recent years, patients with multiple myeloma inevitably relapse. The RNA polymerase II complex has been identified as a promising therapeutic target in both proliferating and dormant cancer cells. Alpha-amanitin, a toxin so far without clinical application due to high liver toxicity, specifically inhibits this complex. Here, we describe the development of HDP-101, an anti-B-cell maturation antigen (BCMA) antibody conjugated with an amanitin derivative. HDP-101 displayed high efficacy against both proliferating and resting myeloma cells in vitro, sparing BCMA-negative cells. In subcutaneous and disseminated murine xenograft models, HDP-101 induced tumor regression at low doses, including durable complete remissions after a single intravenous dose. In cynomolgus monkeys, HDP-101 was well tolerated with a promising therapeutic index. In conclusion, HDP-101 safely and selectively delivers amanitin to myeloma cells and provides a novel therapeutic approach to overcome drug resistance in this disease.
Published online first: December 9, 2020
Gesehen am 08.09.2021